Analisis Program Sertifikasi Halal sebagai Penerapan Etika Bisnis Islam pada Usaha Mikro Kecil di Kab Bangkalan - Umi Khozinatul Khoiriyah; Hildah Meliyana; Muawanah Muawanah; Muhammad Ersya Faraby (Trending: Jurnal Manajemen dan Ekonomi, 2025)
This study analyzes the implementation of the Halal Certification Program as an application of Islamic Business Ethics (IBE) in Micro and Small Enterprises (MSEs) in Bangkalan Regency, Madura. Bangkalan, with its predominantly Muslim population, necessitates business practices aligned with Islamic values, particularly halal and thayyib. Despite the regulatory mandate for halal certification through Law No. 33 of 2014, adoption among MSEs remains low. This research employs a descriptive qualitative approach, gathering data through in-depth interviews and field observations from MSEs in Bangkalan. The study aims to identify the challenges and effectiveness of the Halal Certification Program in fostering sharia accountability at the grassroots level. Findings reveal that while MSEs generally understand the concept of halal, challenges persist in implementation due to limited knowledge, administrative complexities, and perceived high costs. The role of local government and Halal Centers in facilitating certification is crucial but requires enhanced effectiveness. The implications of this study suggest the need for tailored strategies to address these barriers, promote ethical business practices, and enhance consumer trust, thereby supporting the vision of Indonesia as a global halal industry hub.